All-3D-printed solid-state microsupercapacitors - Chae, C.; Kim, Y.-B.; Lee, S.S.; Kim, T.-H.; Jo, Y.; Kim, Hyung seok; Kim, S.-K.; Choi, Y.; Jeong, S. (Elsevier BV, 2021)
Recently, miniaturized electrochemical energy storage units have gained tremendous attention in the fields of microelectronic electronics systems, with the advent of the era of “internet of things”. Shape configurable energy storage devices can be implemented on arbitrarily designable electronics system through 3D printing on the designated surfaces of device systems. In this study, we have developed a methodology of fabricating an all-3D-printed solid-state energy storage device by sequentially printing 3D-printable highly viscous fluids for metallic current collector, electrode and electrolyte layers. The Ni metallic current collector that can be operated stably at a high voltage condition of 3 V, is formed by a combinatorial approach of using 3D printing and 3D laser sintering processes. An intact physical interaction is interpreted comprehensively for the particles residing inside the printed particulate layer and the photons irradiated from a green laser source, based on an in-depth comparative investigation of experimental data and electromagnetic simulation result. A graphene nanoplatelet-based electrode fluid and an ionic liquid-based UV curable electrolyte fluid are printed successively on top of 3D-structured current collectors. It is demonstrated that the all-3D-printed microsupercapacitor device delivers the energy density and power density of 25.4 to 8.5 μWh？cm？2 and 150 to 6,483 μW？cm？2, respectively, even approaching the state-of-the-art level for flat-type conventional devices. ？ 2021 Elsevier B.V.